2000
DOI: 10.1017/s0003598x00060464
|View full text |Cite
|
Sign up to set email alerts
|

Palaeolithic perishables made permanent

Abstract: Previous research has documented textile and basketry production at Moravian Upper Palaeolithic sites, c.27,000 BP. Recent research extends these technologies to Russia and Germany, and amplifies information on perishable fibre artefacts from France. Collectively, these data illustrate the ubiquity of perishable technologies across the late Pleistocene world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…Recent analysis of burnt clay objects from sites such as Pavlov I (Czech Republic), originally recovered during excavations of the early Soviet (Adovasio et al 1996). Additional research has produced more evidence of early perishables, such as textile and basketry production by 28,000 B.P., connected with additional finds from Central Europe, France, and Russia (Soffer et al 2000). These studies have indicated that such technologies were much more widespread across Europe and the western steppe region during the late Pleistocene than previously thought.…”
Section: The Eurasian Steppesmentioning
confidence: 94%
“…Recent analysis of burnt clay objects from sites such as Pavlov I (Czech Republic), originally recovered during excavations of the early Soviet (Adovasio et al 1996). Additional research has produced more evidence of early perishables, such as textile and basketry production by 28,000 B.P., connected with additional finds from Central Europe, France, and Russia (Soffer et al 2000). These studies have indicated that such technologies were much more widespread across Europe and the western steppe region during the late Pleistocene than previously thought.…”
Section: The Eurasian Steppesmentioning
confidence: 94%
“…The genetic analysis of lice 114 suggests that body lice (Pediculus humanus humanus) became differentiated from head lice (Pediculus humanus capitas) about 70,000 years ago, when clothing may have become part of the human wardrobe. Although weaving is thought to be a more recent cultural innova- tion, 115 with evidence of its existence dated at about 28,000 years ago, lice may have lived in the seams of skins that were worn earlier.…”
Section: Pathogen Genomes Shed Light On Their Role In Hominids' Pastmentioning
confidence: 99%
“…Indeed, direct indications for the use of fibers begin to appear in the archaeological record, in extremely small numbers and usually in a very fragmentary state, only at Ϸ26,000 years B.P. in Moravia (11). Inferences to clothing made of perishables that could have included plant fibers followed the study of European Upper Paleolithic female figurines, some of which appear to be clothed (12).…”
Section: Paleolithic Perishablesmentioning
confidence: 99%